The Synchronous Presence of Multiple Myelomas and Other Primary Malignant Tumors: Case Series with Literature Review - Li, Ning (Cancer Manag Res, 2020)
OBJECTIVE: The synchronous presence of multiple myeloma (MM) and other primary malignant tumors (PMTs) were rarely reported. This study aimed to analyze several cases of MM and other PMTs in order to improve clinicians’ understanding of multiple myeloma (MM) with sMPMTs. METHODS: This study was a retrospective trial. We retrospectively analyzed six cases of the synchronous presence of MM and other PMTs and reviewed the literature to summarize the clinical features and treatment. RESULTS: The results showed that five cases of immunoglobulin G (IgG) and one case of kappa light chain; D-S stage: six case of stage III; ISS stage: one case of stage I, two cases of stage II, and three cases of stage III; one case each of gastric cancer (pT2N0MO, stage I), breast cancer (pT1bN0M0, stage I), lung cancer (pT1N0M0, stage I), cervical cancer (stage IB2), thyroid cancer (pT1N0M0, stage I), and diffuse large B-cell lymphoma (Ann-Arbor stage II); three of five patients underwent surgery alone, one patient underwent surgery first and then received chemotherapy at the time of pleural metastasis and the other patient only received radiotherapy; two patients were still alive, three died of progression of MM, and one died of lung cancer. The median survival time was 33.5 months (95% CI, 14.17 to 59.5months). CONCLUSION: The relationship between synchronous MM and other PMTs remains unknown. Clinicians should improve their understanding of MM with sMPMTs by carrying out multidisciplinary collaboration and a patient-oriented approach to optimize treatment and prolong the survival rates of patients.